The Problem of Emancipation : The Caribbean Roots of the American Civil War - Rugemer, Edward Bartlett, 1971- (Book collections on Project MUSE., 2008)
"A most persuasive work that repositions the American debates over emancipation where they clearly belong, in a broader Anglo-Atlantic context."-Reviews in HistoryWhile many historians look to internal conflict alone to explain the onset of the American Civil War, in The Problem of Emancipation, Edward Bartlett Rugemer places the origins of the war in a transatlantic context. Addressing a huge gap in the historiography of the antebellum United States, he explores the impact of Britain's abolition of slavery in 1834 on the coming of the war and reveals the strong influence of Britain's old Atla.